El control patrimonial y su incidencia en la administración de bienes muebles de la Municipalidad Distrital de Usquil año 2017 - Guzmán Avalos, Elsa Yanelí (2019)
The objective of this research is to determine how the Patrimonial Control affects the administration of movable assets of the District Municipality of Usquil year 2017, which allows knowing and identifying all those assets that make up the entity's assets, as well as having updated records. The problem that was investigated is: How does the patrimonial control affect the administration of real estate of the M.D.U. year 2017? And the hypothesis is the patrimonial control affects significantly in a favorable way in the administration of real estate of the M.D.U year 2017. The population or universe of study was the District Municipality of Usquil and the sample was 3 workers of the area of patrimonial control and 10 workers of the different areas of the entity. The analytical-descriptive and synthetic method was used and the techniques used were: interview and bibliographic review. According to the results obtained, they allowed us to know that in the District Municipality of Usquil there are pending assets to be discharged, there are assets that are not written off, the Reconciliation Accounting Equity is not being fulfilled efficiently and with respect to the inventory if perform on the dates indicated, allowing us. It is concluded that the patrimonial control in the District Municipality of Usquil negatively affects the correct administration of the movable property of the entity, thus making it difficult to know how many personal property the entity has for the proper functioning of its activities and maintaining them. Among the recommendations, it was suggested that the corresponding procedures be carried out for the registration and deregistration of the assets of the entity that are pending, the delivery of the Waste Electrical and Electronic Devices to the operators and the Waste Management Systems of Electric Appliances and Electronic, the sanitation of the missing goods and disposing of them.